Application of outcomes research in animal health and veterinary medicine - Dewsbury, Diana Marisa Adele (Kansas State University, 2021)
While it has been well-established in human medicine, ‘outcomes research’ is a relatively recent field of research in animal health and veterinary medicine, hereafter referred to as the animal health industry. Outcomes research has applications in One Health systems, veterinary product development, post-licensure evaluation of veterinary pharmaceuticals and/or biologics, and economic analyses. The major themes of outcomes relevant to the animal health industry include, but are not limited to: health, production, economics, and marketing. Although broad-ranging in terms of animal species, objectives, research methodologies, design, analysis, value, and impact, research studies described herein are all united under the umbrella of outcomes research. Four research chapters are included in this doctoral dissertation, and a very brief summary of the objectives, findings, and impact follow. The objective of the first research chapter was to compare the efficacy of two antimicrobials administered for bovine respiratory disease (BRD) metaphylaxis in stocker calves backgrounded on pastures utilizing a randomized design to evaluate health, production, and economic outcomes. The second research chapter was also a comparative research study; however, canine acceptability of two chewable non-steroidal tablets for the management of canine osteoarthritis (OA) were evaluated. The final two research chapters were food safety studies focusing on Shiga toxin-producing Escherichia coli (E. coli) in cattle. For the third research chapter, the objective was to evaluate the effectiveness of a direct-fed microbial (DFM) product in reducing fecal shedding of E. coli O157:H7 in commercial feedlot cattle in Kansas and Nebraska prior to harvest. Whereas E. coli O157:H7 has been widely researched for over three decades, non-O157 STEC are not as thoroughly examined. Therefore, the objective of the fourth and final research chapter was to gather, integrate, and interpret data on the prevalence and concentration of the Top 6 non-O157 serogroups (O26, O45, O103, O111, O121, and O145) and associated virulence genes (stx1, stx2, and eae) in fecal, hide, and carcass samples of pre- and peri-harvest adult cattle worldwide, using a systematic review of the literature, meta-analysis, and meta-regression analyses. In summary, the chapters in this doctoral dissertation have impacted the fields of animal health, veterinary medicine, and One Health (via food safety research). The first research chapter compared two licensed antimicrobial products used in typical production conditions and management practices while measuring outcomes relevant to veterinarians and producers in the beef industry with externally valid research findings. Similarly, the second research chapter supported the hypothesis that canine acceptability between two bioequivalent pharmaceutical products were comparable. The ease of voluntary prehension of chewable tablets by canines is conducive to long-term management of OA symptoms and increases pet-owner compliance to the treatment protocol, both key factors for long term efficacy and management of OA symptoms, in addition to the generic formulation being a more affordable option. In terms of food safety efforts, whereas the DFM product of interest in the third research chapter was not effective in reducing the prevalence and/or concentration of E. coli O157:H7 in cattle feces, the effectiveness of this DFM product in finishing feedlot cattle in the commercial environment was successfully evaluated. Lastly, the fourth research chapter generated data that contributes to quantitative microbial risk assessment models, provides evidence that is highly valued in expert panels, and offers robust estimates of the frequency of these non-O157 STEC pathogens, regionally and globally, while demonstrating the existing knowledge gaps for prevalence and concentration of these pathogens in hide and carcass matrices. Research studies presented in this doctoral dissertation highlight the versatility of outcomes research while emphasizing the widespread impact outcomes research has on the animal health industry globally.
Keywords: Outcomes research; Animal health industry